2000
DOI: 10.1016/s0005-2728(00)00103-1
|View full text |Cite
|
Sign up to set email alerts
|

Proton translocating nicotinamide nucleotide transhydrogenase from E. coli. Mechanism of action deduced from its structural and catalytic properties11This review is dedicated to the memory of Professor Lars Ernster.

Abstract: Transhydrogenase couples the stereospecific and reversible transfer of hydride equivalents from NADH to NADP(+) to the translocation of proton across the inner membrane in mitochondria and the cytoplasmic membrane in bacteria. Like all transhydrogenases, the Escherichia coli enzyme is composed of three domains. Domains I and III protrude from the membrane and contain the binding site for NAD(H) and NADP(H), respectively. Domain II spans the membrane and constitutes at least partly the proton translocating path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 85 publications
0
35
0
Order By: Relevance
“…Thus, as the dIII in one trimer enters the open state to permit product release and substrate binding, the other enters the occluded state to permit hydride transfer; the two trimers run 180 o out of phase. In general, a mechanism of coupling involving changes in NADP(H) binding is also favored by other authors (17)(18)(19).…”
mentioning
confidence: 66%
“…Thus, as the dIII in one trimer enters the open state to permit product release and substrate binding, the other enters the occluded state to permit hydride transfer; the two trimers run 180 o out of phase. In general, a mechanism of coupling involving changes in NADP(H) binding is also favored by other authors (17)(18)(19).…”
mentioning
confidence: 66%
“…Approximately 45% of NADPH in the mitochondria is produced by nicotinamide nucleotide transhydrogenase (Nnt) and the remainder comes from NADP ϩ -isocitrate dehydrogenase 2 or mitochondrial NAD(P)-malic enzyme (16,17). What separates Nnt from the other mechanisms of NADPH production is it utilizes the proton gradient generated through the citric acid cycle and the electron transport chain to convert NADP ϩ into NADPH (18,19). The role of Nnt in mitochondrial redox regulation has been demonstrated previously in studies, which showed that Nnt inhibition decreased GSH redox status and increased sensitivity to oxidative stress; however, its role in modulating the Trx/ Prx system in brain mitochondria remains unknown (16, 20 -22).…”
Section: Mitochondrial Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Transhydrogenase from E. coli is composed of an ␣ subunit (PntA, 54 kDa) and a ␤ subunit (PntB, 48 kDa), building an active form of ␣ 2 ␤ 2 . As is the case for all proton-translocating transhydrogenases, the enzyme is composed of three domains: the hydrophilic domain I (for E. coli, ␣1 to ␣402) containing the NAD(H) binding site, a hydrophobic domain II (for E. coli, ␣-403 to ␤260) harboring the membrane spanning ␣-helices, and a hydrophilic domain III (for E. coli, ␤261 to ␤462) containing the NADP(H) binding site (6).…”
Section: Vol 77 2011mentioning
confidence: 99%